"MY MAIN JOB IS TO TRANSLATE / PAIN INTO TALES THEY CAN TOLERATE // IN ANOTHER LANGUAGE": women's poetry and the health humanities. Issue 1 (2nd January 2017) - Dowson, Jane
Abstract: This article examines the contribution that poetry written over the last fifty years might make to the established and burgeoning field of Medical Humanities. It takes poems by women about cancer and depression as a case study of how they can offer insight into the impact of these conditions on the sufferer. Collectively, the poems document and effect shifts in knowledge about, and the associated stigmas concerning, illnesses that carry secrecy and shame, specifically cancer and depression. Additionally, drawing on Virginia Woolf's remarkable essay "On Being Ill" (1930), we see how the non-verbal features of poems, particularly metaphors and symbols, mark the space of what a patient cannot fully articulate. Accordingly, the poems discussed illuminate how literature can express human interiority but at the same time remind the reader – or health professional – that interiority can never be fully presented. Thus, poetry both contributes to and also checks the ways in which literature is appropriated by the biomedical sciences. The poets included are Eavan Boland, Julia Darling, U.A. Fanthorpe, Jackie Kay, Gwyneth Lewis, Carol Satyamurti and Jo Shapcott. Some poems specify a female subjectivity, some express agency as autonomous individuals, while others presume to speak of common human experience.